2014
DOI: 10.17511/ijmrr.2014.i03.09
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of abdominal organs in a sickle cell disease patient

Abstract: Background: SCD is one of the most common inherited hemoglobinopathies worldwide. It is a major health problem in Madhya Pradesh and surrounding states. The present study was undertaken to infer the value of ultrasonography in evaluating abdominal organs in a SCD patient. Study design: This is a prospective hospital based study. Method: 100 SCD patients were assessed for abdominal pathologies by USG, the results thus analyzed and prevalence was calculated. Result: Hepatomegaly is the most common association ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The frequency of non-visualised spleens in our study was also similar to those reported in patients with SCD in Turkey (42.9%) [31] and the United States (35.7%) [32]. Lower frequencies have been found in Asia (11%) [33], the Middle-East (6.1%) [12] and the United States (9%) [21]. The variability of splenic nonvisualisation on ultrasonography in the different geographic location may partly be explained by the presence of genetic factors known to inhibit sickling, such as alphathalassaemia and HbF [11,20], improvement in clinical care and outcomes in SCD [21,32], and also environmental factors that results in the frequent exposure to organisms known to cause spleen enlargement including malaria and bacterial infections [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of non-visualised spleens in our study was also similar to those reported in patients with SCD in Turkey (42.9%) [31] and the United States (35.7%) [32]. Lower frequencies have been found in Asia (11%) [33], the Middle-East (6.1%) [12] and the United States (9%) [21]. The variability of splenic nonvisualisation on ultrasonography in the different geographic location may partly be explained by the presence of genetic factors known to inhibit sickling, such as alphathalassaemia and HbF [11,20], improvement in clinical care and outcomes in SCD [21,32], and also environmental factors that results in the frequent exposure to organisms known to cause spleen enlargement including malaria and bacterial infections [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…Whereas most studies used spleen length to define splenomegaly in SCD (10)(11)(12)(13)(14)(15)(16)(17)36), others used spleen volume (18,19,37,38) or both length and volume (31)(32)(33). Given the strong positive correlation between spleen length and volume in our normal controls (rho = 86.4; P = 0.0001), consistent with earlier reports (26,39), both parameters were used to classify spleen sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Other diagnostic modalities used in the radiological assessment of the spleen include CT and MRI scan (7)(8)(9), however, routine use of CT or MRI imaging is not feasible in most developing countries because of high cost and limited availability. Despite the widespread use of ultrasonography in the clinical evaluation of splenic enlargement, there is no consensus on how to define splenomegaly among SCD patients, as various cut-off values have been used in the literature (10)(11)(12)(13). Some studies have considered a spleen length of 13 cm to indicate enlarged spleens (10,11,14,15), while others have defined splenic enlargement as a spleen length of > 11cm (12) or > 12 cm (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…echogenic foci in the studies by Gale et al and30 Kaushal et al may be due to difference in geographical locations, as their studies were carried out in the United states and India, respectively. In 24 addition, study conducted by Gale et al was a retrospective, three-year study, with inclusion of patients on treatment with hydroxyurea, which may also affect the splenic echopattern.…”
mentioning
confidence: 93%